2021
DOI: 10.48550/arxiv.2111.01809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutron-capture elements record the ordered chemical evolution of the disc over time

Danny Horta,
Melissa K. Ness,
Jan Rybizki
et al.

Abstract: The joint abundance-kinematic-age measurements of stars provide the means to link the chemical to the environmental and structural evolution of the Galaxy. An ensemble of nucleosynthetic channels can be leveraged to build a comprehensive chemical account. Using GALAH DR3, we study the element abundances of [Fe/H], [𝛼/Fe], [Ba/Fe], and [Eu/Fe] of ∼50,000 red giant stars, as tracers of the enrichment by supernovae Ia, supernovae II, asymptotic giant branch stars, neutron-star mergers and/or collapsars. We chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Several further works have contributed to the understanding of the origin of this growth, without yet reaching a general consensus, arguing whether the enrichment is due to mixing effects that produce a larger source of neutrons, and hence s-elements, in low-mass stars, or whether it is due to observational effects or related to stellar characteristics, such as chromospheric or magnetic activity (see, e.g., Busso et al [9], Bisterzo et al [25], Mishenina et al [26], Trippella et al [27], Reddy and Lambert [28], Magrini et al [29], Spina et al [30,31], Baratella et al [32]). Other works used the properties of those abundance ratios as a valuable tool to estimate the ages of stars (see, e.g., Spina et al [30], Nissen [33], Delgado Mena et al [34], Casali et al [35], Horta et al [36]).…”
Section: Age Effects In the Abundances Of The S-process Elementsmentioning
confidence: 99%
“…Several further works have contributed to the understanding of the origin of this growth, without yet reaching a general consensus, arguing whether the enrichment is due to mixing effects that produce a larger source of neutrons, and hence s-elements, in low-mass stars, or whether it is due to observational effects or related to stellar characteristics, such as chromospheric or magnetic activity (see, e.g., Busso et al [9], Bisterzo et al [25], Mishenina et al [26], Trippella et al [27], Reddy and Lambert [28], Magrini et al [29], Spina et al [30,31], Baratella et al [32]). Other works used the properties of those abundance ratios as a valuable tool to estimate the ages of stars (see, e.g., Spina et al [30], Nissen [33], Delgado Mena et al [34], Casali et al [35], Horta et al [36]).…”
Section: Age Effects In the Abundances Of The S-process Elementsmentioning
confidence: 99%
“…Additionally, comparisons between the slope in the [Fe/H]-[X/Fe] relation and the slope in the age-[X/Fe] relation appear to group elements accordingly into three distinct nucleosynthetic sites: core-collapse supernova (SNe II), white dwarf explosion (SNIa), and stellar winds (Sharma et al 2022). Furthermore, the slope in the age-[X/Fe] relation is sensitive to the location across the [Mg/Fe] vs [Fe/H] plane (Yuxi et al 2021;Horta et al 2021), but the scatter around these relations is consistently small. Both the high resolution studies at [Fe/H] = 0 dex from Nissen (2015) and Bedell et al (2018) as well as the larger samples exploring a wider range of metallicities (Ness et al 2019;Sharma et al 2022) have shown that the intrinsic scatter of stars around their age-[X/Fe] relations is on the order of < 0.01-0.04 dex.…”
Section: Introductionmentioning
confidence: 99%
“…While some chemical thin disc stars may be found in the geometric thick disc, it is characterized by old, α-enhanced, and kinematically hot populations, while the geometric thin disc mostly consist of younger, solar-α, and kinematically cooler populations (e.g., Bensby et al 2005;Lian et al 2020b). This connection between the geometric and chemical dichotomy implies close relation between the thick/thin disc structure formation and the chemical evolution history of the Galaxy (Lian et al 2020b;Horta et al 2021).…”
Section: Introductionmentioning
confidence: 87%